Laser-Carved Legacy: Exploring the Scientific Construction and Cultural Significance of the World’s Largest Golden Buddha in Thailand Through a Tourist Perspective - White, Pattarinee; Phae-Ngam, Wuttichai; Kamoldilok, Surachart; Naemchanthara, Kittisakchai; Limsuwan, Pichet; Suanpang, Pannee (My University, 2025)
This research investigates the intersection of construction innovation and cultural heritage through the lens of tourist perceptions of the world’s largest carved golden Buddha, situated at Khao Chi Chan Mountain, Pattaya, Thailand. Positioned as an emerging tourism destination, this site contributes to the rebranding of Pattaya as a globally significant hub for religious tourism. This study highlights how this monumental Buddha statue fosters spiritual experiences, promotes the conservation of art and culture, and encapsulates a historical narrative tied to Thailand’s royal lineage. Notably, the statue’s creation employed a pioneering technique—the only one of its kind worldwide—involving laser-guided carving by artisans, followed by gold leaf application to enhance its aesthetic magnificence. A mixed-methods research approach was adopted, integrating historical document analysis with narrative accounts of the statue’s construction using modern technology, complemented by quantitative data collected through tourist questionnaires. By documenting the historical use of laser technology in creating this iconic Buddhist landmark, this research corrects misconceptions about its construction process and highlights the innovative application of a 20 W Argon ion laser for drawing the image of Buddha on the cliff. This study evaluates tourist perceptions using the DHARMA model, revealing how Destination Identity, Heritage Values, and Memorable Experiences foster emotional connections and spiritual enrichment (β = 0.801, p < 0.001). The findings underscore Khao Chi Chan’s potential to reposition Pattaya as a hub for Buddhist tourism, diversifying its image beyond nightlife-centric tourism. This work contributes to sustainable tourism by demonstrating how sacred sites can balance cultural preservation and economic vitality, offering insights for heritage management and urban tourism development in Southeast Asia.
Keywords: construction innovation; King Bhumibol Adulyadej; religious tourism; spiritual experience; Thailand tourism